Mouse models of chronic wasting disease: A review - Cook, Makayla; Hensley-McBain, Tiffany; Grindeland, Andrea (Frontiers in Virology, 2023)
Animal models are essential tools for investigating and understanding complex prion diseases like Chronic Wasting Disease (CWD), an infectious prion disease of cervids (elk, deer, mouse, and reindeer). Over the past several decades, numerous mouse models have been generated to aid in the advancement of CWD knowledge and comprehension. These models have facilitated the investigation of pathogenesis, transmission, and potential therapies for CWD. Findings have impacted CWD management and disease outcomes, though much remains unknown, and a cure has yet to be discovered. Studying wildlife inherently lacks the reproducibility of a controlled laboratory setting; therefore, using mouse models in many cases is the first step to understanding the mechanisms of disease. Here, we provide a comprehensive review of studies with mouse models in CWD research. We begin by reviewing studies that examined the tissues, bodily fluids, and excreta that spread disease, then address routes of infectivity and infectious load. Next, we delve into studies of genetic factors that may influence protein structure. We then move on to immune factors, possible transmission through environmental contamination, and species barriers and differing prion strains. We conclude with studies that make use of cervidized mouse models in the search for therapies for CWD.